Periprosthetic joint infection in total ankle replacement: which are the current diagnostic criteria? Infection in Ankle Replacement - Izzo, Antonio; Di Gennaro, Donato; Sgadari, Arianna; Coviello, Antonio; Marasco, Domenico; Balato, Giovanni; Mariconda, Massimo; Bernasconi, Alessio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Periprosthetic joint infection (PJI) is among the most common complications of Total Ankle Replacement (TAR) and its management may be challenging. We set out to define which are the criteria currently used to diagnose PJI after TAR. Methods: This PRISMA-compliant systematic review was registered in the Open Science Framework. Multiple databases were searched including clinical studies in which PJI after TAR was diagnosed and treated. Data were harvested regarding the cohort, the study design and the diagnostic criteria for PJI. Risk of bias was assessed using the modified Coleman Methodology Score (mCMS). Results: Six papers (122 infected TARs) published between 2012 and 2022 were included in this review. Ankle pain with swelling and unexplained increased local temperature were the most common clinical findings leading to a suspicion of PJI. In 100% of cases the diagnosis was confirmed through synovial fluid analysis associated with positive blood tests. In all the revision surgeries intraoperative cultures (at least 3) were performed. In 109 ankles (90%) there was a microbiological isolation. Out of these, 38 (35%) were single organism infections by Staphylococcus coagulase negative and 37 (34%) were single organism infections by Staphylococcus Aureus. The mean mCMS was 37.6 out of 100. Conclusions: There is a lack of diagnostic criteria specific for PJI after TAR. Clinical and laboratory tests inspired to the knowledge in total knee and total hip arthroplasty are generally adopted in the field of ankle arthroplasty. The quality of evidence for studies included in this review was poor.